Auto-determinação e reabilitação psicossocial de pessoas com esquizofrenia - A. Marques (2006)
The purpose of this study was to characterize portuguese psychosocial rehabilitation responses for people with psychiatric disabilities, to clarify the understandings of the different intervenient in psychosocial rehabilitation processes (principles, values, and believes grounding rehabilitation), and to analyse the self-determination of people with psychiatric disabilities integrated in different psychosocial rehabilitation programs. A questionnaire was applied directly to 120 rehabilitation professionals, 198 persons with schizophrenia, and to 13 portuguese psychiatric rehabilitation institutions. The results revealed significant differences in the way patients and professionals perspective and value the rehabilitation process, particularly in various dimension of objectives, strategies, and users involvement. In what concerns the rehabilitation responses, most of the institutions are located in an urban context, assured by non governmental organisations, and offer professional training programs. Concerning self-determination level, most of the users demonstrate not to have total control over their life, and the multidimensional disability produced by the disease, the stigma associated, and the lack of social responses seem to be some of the factors contributing to this situation.